Warrior girl unearthed eaudiobook - Boulley, Angeline (Macmillan Young Listeners, 2023)
Named One of BookPage 's Best Audiobooks of 2023 "Actor Isabella Star LaBlanc excels at leading the reader deeper into the story with a tone that exudes both intriguing mystery and genuine emotion." — BookPage "Isabella Star LaBlanc, a Sisseton Wahpeton Dakota narrator, accurately delivers Native intonations and rhythms while narrating a second book about an Indigenous heroine from Sugar Island, Michigan. LaBlanc excels at weaving a gripping plot, Perry's snarky wisdom, and a lyrical blending of languages." — AudioFile Magazine (Earphones Award Winner) "LeBlanc's captivating voice draws readers in, expressing every mundane, sweet, heartbreaking, and life-threatening moment." — School Library Journal From the New York Times bestselling author of Firekeeper's Daughter comes a thrilling YA mystery about a Native teen who must find a way to bring an ancestor home to her tribe. Perry Firekeeper-Birch was ready for her Summer of Slack but instead, after a fender bender that was entirely not her fault, she's stuck working to pay back her Auntie Daunis for repairs to the Jeep. Thankfully she has the other outcasts of the summer program, Team Misfit Toys, and even her twin sister Pauline. Together they ace obstacle courses, plan vigils for missing women in the community, and make sure summer doesn't feel so lost after all. But when she attends a meeting at a local university, Perry learns about the "Warrior Girl", an ancestor whose bones and knife are stored in the museum archives, and everything changes. Perry has to return Warrior Girl to her tribe. Determined to help, she learns all she can about NAGPRA, the federal law that allows tribes to request the return of ancestral remains and sacred items. The university has been using legal loopholes to hold onto Warrior Girl and twelve other Anishinaabe ancestors' remains, and Perry and the Misfits won't let it go on any longer. Using all of their skills and resources, the Misfits realize a heist is the only way to bring back the stolen artifacts and remains for good. But there is more to this repatriation than meets the eye as more women disappear and Pauline's perfectionism takes a turn for the worse. As secrets and mysteries unfurl, Perry and the Misfits must fight to find a way to make things right – for the ancestors and for their community. A Macmillan Audio production from Henry Holt & Company.